Memory function in patients with opioid dependence treated with buprenorphine and methadone in comparison with healthy persons - Sara Kamali Ardakani; Sara Mahmoudi; Khaled Rahmani; Narges Shamsalizadeh (Scientific Reports)
Abstract Methadone and buprenorphine are commonly used for drug abuse treatment but may impair cognitive function. This study assessed memory performance in patients receiving these treatments compared to healthy controls. A cross-sectional study was conducted on 93 buprenorphine- and 120 methadone-treated patients, compared with 120 healthy controls. The Wechsler Memory Scale was used, and scores were compared among the study groups using Kruskal–Wallis with Tukey’s post-hoc test. Maintenance therapy duration was compared between case groups using an independent t-test or Mann–Whitney U test. Healthy controls were superior to both treatment groups in mental control. The methadone group surpassed controls in personal and general information (P < 0.05), while buprenorphine-treated patients scored lower in associate learning. Patients receiving methadone for > 2 years had a higher mean score of awareness of place and time than those on long-term buprenorphine (P = 0.034). Longer buprenorphine treatment correlated with improved total memory scores (P = 0.03). The mental test showed no significant adverse effect for either medication on most mental aspects, except for mental control, which was worse than the control group in both medications. In some aspects, treated patients even outperformed controls. Buprenorphine preserves memory function better than methadone over time.